Enhancing Activity of Pd-Based/rGO Catalysts by Al-Si-Na Addition in Ethanol Electrooxidation in Alkaline Medium - Minh Dang Nguyen; Lien Thi Tran; Quang Minh Nguyen; Thao Thi Nguyen; Thu Ha Thi Vu (Journal of Chemistry)
The article presents modified Pd-based catalysts supported on reduced graphene oxide (rGO), used in the electrooxidation reaction of ethanol in alkaline medium. When NaBH4 reducing agent was used, the random presence of Na was found out. According to this result, Na was used as a promoter of Pd-based catalyst. Consequently, the Al-Si-Na addition not only assisted active phase Pd nanoparticles to disperse homogenously on graphene surport, but also contributed to increase catalytic activity in the reaction. This value, 16138 mA·mg−1Pd, is about 1.5 times higer than that of the catalyst modified by Al-Si. Moreover, the stability of the catalyst is enhanced more. The electrochemical stability of PASGN.N catalyst was relatively good: after 500 scanning cycles, the current density diminished 32% compared with the highest peak current density of the 15th cycle, which was chosen as a reference. These significant improvement results in electrooxidation of ethanol have opened up the high potential application of these catalysts in direct-ethanol fuel cell.